2011
DOI: 10.1002/bimj.201000152
|View full text |Cite
|
Sign up to set email alerts
|

An overview of techniques for linking high‐dimensional molecular data to time‐to‐event endpoints by risk prediction models

Abstract: Analysis of molecular data promises identification of biomarkers for improving prognostic models, thus potentially enabling better patient management. For identifying such biomarkers, risk prediction models can be employed that link high-dimensional molecular covariate data to a clinical endpoint. In low-dimensional settings, a multitude of statistical techniques already exists for building such models, e.g. allowing for variable selection or for quantifying the added value of a new biomarker. We provide an ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 109 publications
(103 reference statements)
0
14
0
Order By: Relevance
“…This paper illustrates that binary classifiers highly depended on how the risk groups were defined. Binder et al [30] investigated the effects of the choice of threshold on the predictions and showed that there is little overlap of selected genes between an early and median threshold cutoffs, which might be due to short-term and long-term effects of genes or the censoring pattern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper illustrates that binary classifiers highly depended on how the risk groups were defined. Binder et al [30] investigated the effects of the choice of threshold on the predictions and showed that there is little overlap of selected genes between an early and median threshold cutoffs, which might be due to short-term and long-term effects of genes or the censoring pattern.…”
Section: Discussionmentioning
confidence: 99%
“…A slight change of the threshold can lead to very different prediction accuracy and interpretation. Binder et al [30] applied three different survival thresholds to evaluate a binary classifier based on gene expression, and showed how the choice of threshold affected the predictions. They concluded that using the binary modeling approach can result in loss of efficiency and potential bias in high dimensional settings.…”
Section: Introductionmentioning
confidence: 99%
“…For a more general overview of such approaches, see e.g. Binder et al [7] and for a comparison of the most common methods see Bøvelstad et al [8] or van Wieringen et al [9]. We will specifically consider the lasso [10] and componentwise likelihood-based boosting [11], [12] as representative approaches for regularized regression with variable selection.…”
Section: Introductionmentioning
confidence: 99%
“…Especially when probability estimation is derived via machine learning methods the noninformation error provides valuable information on the potential amount of overfitting and resulting overoptimism that can be inherited when these techniques are not properly tuned. So we find ourselves in a similar situation as with, for example, regularized regression models such as the Lasso (Tibshirani, ) or boosting (Binder et al., ). This makes a unifying view of all these approaches as flexible statistical models useful.…”
mentioning
confidence: 85%